ANALYSIS OF PRESUPPOSITION IN THE Q&A SESSION OF JOE BIDEN'S SPEECH ON FEBRUARY 25th 2022 ON THE NBC NEWS YOUTUBE CHANNEL DECLAIMING THE RUSSIAN INVASION OF UKRAINE - Jawas, Azizah; Ratih P, Shita Dewi; Taufik, Maulana (Universitas Pakuan, 2024)
Fluency in communication cannot be separated from the influence of presuppositions. The presupposition is something that the speaker assumes as an event before the utterance. This study aims to identify and describe the types of presuppositions and common ground in a question-and-answer session between journalists and President Joe Biden at a press conference of Joe Biden's speech denouncing Russia's invasion of Ukraine. To meet this purpose, the researchers applied George Yule's theory (1996) and utilized the descriptive method with a notetaking technique as a data collection technique where the data source is in the form of a video. The results showed 5 types of presuppositions in 26 presuppositions data from 17 speeches data analyzed.